Bone mineral density in patients with interstitial lung disease - Alhamad, Esam H; Nadama, Rufai (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Objective: To determine the prevalence of low bone mineral density (BMD) and the risk factors for osteoporosis in patients with interstitial lung disease (ILD). Methods: Consecutive newly diagnosed ILD patients (n=196) were included in the study. Detailed demographic and clinical data were collected at the time of diagnosis, along with BMD measurements. Univariate and multivariate logistic regression analyses were used to determine the risk factors for osteoporosis. Results: Forty-four percent of the patients had osteoporosis, and 36% had osteopenia. The diagnosis of usual interstitial pneumonia (UIP) was more frequently observed in the patients with osteoporosis than in those without osteoporosis (67 vs. 47%, respectively; p=0.005). The univariate analyses identified the following five variables that were associated with an increased risk of osteoporosis at any site: older age (odds ratios [OR], 1.06; 95% confidence intervals [CI], 1.04 - 1.09; p